Effects of Different Polishing Procedures on the Surface Roughness and Hardness of Polyether Ether Ketone (PEEK) - Ozdogan, Alper (2020)
There is insufficient information about the chairside polishing methods of polyether ether ketone material. Therefore, it is aimed in this study to investigate the effects of different polishing processes on polyether ether ketone surface roughness and hardness. A total of 66 disc-shaped specimens made of polyether ether ketone were used in this study. The specimens were polished conventionally and randomly divided into three groups (n=22). One group was designated as the control group, and no further treatment was applied. In the other two groups, the specimens’ surfaces were abraded with diamond burs and polished using two different polishing kits. Their surface roughness and Vickers hardness were measured, and environmental scanning electron microscopy and atomic force microscopy examinations were performed. The data were statistically analysed using analysis of variance and Tukey’s honest significant difference test (α=0.05). There were no statistically significant differences between the control and polishing kit groups in terms of either surface roughness or Vickers hardness (p>0.05). The polishing kits can be used reliably and effectively for polishing polyether ether ketone materials.